Correlation of ETL in perovskite light-emitting diodes and the ultra-long rise time in time-resolved electroluminescence. (15th June 2018) - Wang, Minhuan; Bian, Jiming; Feng, Yulin; Zhang, Yadong; Liu, Hongzhu; Shi, Yantao
Abstract: Here, two series CH3 NH3 PbI3 based perovskite light-emitting diodes (Pe-LEDs) were synthesized with TiO2 and SnO2 as electron transport layer (ETL), respectively. An exceptional ultra-long rise time ( T r ) persisting to tens of seconds was observed in time-resolved electroluminescence (EL) characteristics from the Pe-LEDs as driven with constant voltage, which might be intrinsic to the MAPbI3 perovskite layer regardless of the ETL materials. Qualitatively, SnO2 based ETL was preferred than the TiO2 ETL counterpart for faster response Pe-LED devices with lower Tr . Moreover, the T r of Pe-LED can be adjusted in the range of 10–28 s by precisely controlling the thickness of SnO2 ETL. In addition, the similar trend was also confirmed in the SnO2 ETL thickness dependent hysteresis index deduced from current-voltage ( J-V ) characteristics. The mechanism was interpreted by means of dynamics of carrier injection and transport at the perovskite/ETL interface. These achievement may contribute to better understanding of the origin and mechanism of the slow process in EL characteristics, and hence favorable for minimizing this detrimental effects.